Roles of autoinducer-2 mediated quorum sensing in wastewater treatment - Yirong Liu; Huizhi Hu; Feng Luo (Water Science and Technology, 2021)
Quorum sensing (QS) is considered to be a promising regulation method for biological wastewater treatment (WWT) due to its regulation in extracellular substances (EPS) production, biofilm formation, granulation, colonization and bacterial activity and stability. Recently, autoinducer-2 (AI-2), a kind of interspecies communication QS signal molecule, is being increasingly reported for its roles in regulating bacterial gene expression and aggregation. Consequently, AI-2 mediated QS system is considered as a promising regulatory approach in WWT processes. This article systematically reviews the effects of AI-2-mediated QS system on bacterial behavior and its high potential for real-world applications in different WWT systems. Given the extensive presence of AI-2, AI-2 mediated QS could cooperate with other signal molecules in WWT processes, which suggests that the interactions among multiple signal molecules might be underestimated in the previous studies. The differences between AI-2 and AHL signaling molecules are also compared. Furthermore, the attempts at AI-2 regulated QS in pollution control of different WWT systems are summarized, while some challenges and defects still require targeted research in the future. HIGHLIGHTS The AI-2 mediated QS is a potential regulatory approach in WWT processes.; The differences between AI-2 and AHL signaling molecules are compared.; The interaction among multiple signal molecules might be underestimated in the previous studies.; Possible applications of QQ mechanism based on AI-2 need to be further studied.;